Extensive Bilateral Intracranial Calcifications: A Case of Iatrogenic Hypoparathyroidism. (24th February 2013) - Zisimopoulou, Vaso; Siatouni, Anna; Tsoukalos, Grigorios; Tavernarakis, Antonios; Gatzonis, Stylianos
Abstract : This is a case of a 69-year-old male patient with long-standing iatrogenic hypoparathyroidism after total thyroidectomy. The clinical evaluation revealed mild neurological symptoms and excessive brain calcinosis. Intracranial calcification that affects structures other than the basal ganglia and the cerebellum is a rare manifestation of postoperative hypoparathyroidism. Detection of brain calcinosis in patients who had total thyroidectomy can motivate clinicians in further investigation of possible hypoparathyroidism with measurement of calcium and phosphorus serum levels.